Caracterização da interface da solda de amanteigamento do aço SAE 8630M com inconel 725 pelo processo de soldagem MIG - Martins, Anne Karyne Cunha (2018)
The microstructural characterization of the weld interface is not a condition characterized by norms that govern the application of steels in the oil and gas sector. Due to the report of faults occurring in these components and attributed to the considerable influence of the microstructure on the mechanical properties of the welded component, several researches have been developed to determine the best welding procedure that results in components with mechanical properties appropriate to the application in such aggressive environments mechanical and chemically. Due to this, this work has the objective of analyzing the mechanical and microstructural behavior of the buttery soldering interface used in dissimilar joints for applications in offshore structures submitted to cathodic protection. The GMAW welding process was used in the brazing of SAE 8630M with the consumable AWS ERNiCrMo-15 (Inconel 725). For protection of the arc and the melt pool was used the mixture 75% Ar + 25% He. The influence variables were the stress relief thermal treatment (with TTAT and without TTAT) and the current mode (conventional and pulsed). The response variables analyzed are microstructure, microhardness and hardness. As a result, the use of TTAT was not necessary for the samples, considering that it generated a higher frequency of zones susceptible to cracks and did not guarantee desired levels of microhardness (HV0,025) in these partially diluted zones (ZPDs).